Potensi Pewarna Alami Sebagai Pemanfaatan Hasil Alam Taman Nasional Bukit Baka Bukit Raya - Muflihati, Muflihati; Nurhaida, Nurhaida; Munadian, Munadian (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2024)
The management of National Parks which have special regulations means that village communities around the area have limitations in utilizing the potential of the forests around where they live, as a result, conflicts often occur between village communities and National Park managers. It is necessary to find a solution to utilize a more diverse range of forest products without having to violate the rules for managing national parks. One of the non-timber forest products that has quite high potential for improving the economic level of society is natural dyes that can be extracted from various kinds of resources in the forest. Bukit Baka Bukit Raya National Park has very abundant natural resources so efforts are needed to utilize these natural resources sustainably. For this reason, the PKM Forestry team, in collaboration with the TNBBBR management, carries out outreach on the potential of natural dyes as a use of natural products based on regional potential in improving the economy of the community of Belaban Ella Village, Belaban Resort, Bukit Baka Bukit Raya National Park. It is hoped that this outreach can increase the community's capacity to utilize forest products that are environmentally friendly and of course have high economic value. This outreach can change people's mindset to start exploiting the potential that exists in the forest in an environmentally sustainable way.